2019
DOI: 10.1021/acsnano.8b08253
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Healing of Defects in Atomically Thin GaSe and InSe

Abstract: GaSe and InSe are important members of a class of 2D materials, the III-VI metal monochalcogenides, which are attracting considerable attention due to their promising electronic and optoelectronic properties. Here an investigation of point and extended atomic defects formed in mono-, bi-, and few-layer GaSe and InSe crystals is presented. Using state-of-the-art scanning transmission electron microscopy (STEM), it is observed that these materials can form both metal and selenium vacancies under the action of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 73 publications
(131 reference statements)
3
44
0
Order By: Relevance
“…20,33,51,54,56 Recently, both theoretical calculations and experimental scanning transmission electron microscopy (STEM) reported that the selenium vacancies V Se in InSe crystals can be passivated by chemical dissociation of O atoms at these sites. 20,22,51 Similarly, Po-Hsun et al demonstrated that the change of Raman and X-ray photoelectron spectra (XPS) of pristine InSe flakes exposed to ambient air is comparable to that observed when exposing InSe to dry oxygen atmosphere. The authors attribute these observations to the formation of a surficial InSe 1Àx O x layer that encapsulates the InSe beneath and promotes a long-term stability of thin InSe devices.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…20,33,51,54,56 Recently, both theoretical calculations and experimental scanning transmission electron microscopy (STEM) reported that the selenium vacancies V Se in InSe crystals can be passivated by chemical dissociation of O atoms at these sites. 20,22,51 Similarly, Po-Hsun et al demonstrated that the change of Raman and X-ray photoelectron spectra (XPS) of pristine InSe flakes exposed to ambient air is comparable to that observed when exposing InSe to dry oxygen atmosphere. The authors attribute these observations to the formation of a surficial InSe 1Àx O x layer that encapsulates the InSe beneath and promotes a long-term stability of thin InSe devices.…”
Section: Introductionmentioning
confidence: 89%
“…[43][44][45][46][47][48][49] Similarly, in the case of InSe, the defects related to In adatoms and Se vacancies, which can be related to the In-rich atmosphere in which high-quality InSe crytals are grown, 50,51 may play important roles during the photocurrent generation process in thin InSe photodetectors. 20,[50][51][52] Interestingly, the presence of defects in InSe crystals, especially selenium vacancies (V Se ), 22 is predicted to promote the physical adsorption and chemical dissociation of O 2 /H 2 O molecules and V Se can act as preferential sites for the adsorption of these molecules. 20,[52][53][54][55] This phenomenon can help in explaining the performance degradation reported in various studies on thin InSe devices.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have shown relatively high electron mobilities, strong second harmonic generation in monolayers and a direct bandgap in bulk form which transitions to a quasi-direct bandgap when reduced to the monolayer limit. [4] These properties have been successfully applied in few-layer photodetection and field effect devices and when used together in GaSe/InSe heterostructures have shown tunable photoemission from interlayer excitons. The performance of devices based on GaSe and InSe can be affected by the presence of impurities or by exposure to air, light, and/or moisture, yet, little has been done to characterise the structure of these defects.…”
mentioning
confidence: 99%
“…The performance of devices based on GaSe and InSe can be affected by the presence of impurities or by exposure to air, light, and/or moisture, yet, little has been done to characterise the structure of these defects. We have used atomic resolution STEM together with electron energy loss spectroscopy (EELS) and energy dispersive X-ray spectroscopy to characterise individual point and extended defects in these materials [4]. By analysing annular dark field (ADF) STEM images of mono-, bi-, and few-layer GaSe and InSe crystals we observe that these materials can form both metal and selenium vacancies under the action of the electron beam.…”
mentioning
confidence: 99%
See 1 more Smart Citation